Participation in Population-based Research: A Qualitative, Intersectional Perspective. (20th October 2021) - Merz, S; Jaehn, P; Holmberg, C
Abstract: Background: Intersectionality scholarship in public health research aims at making visible the interrelated and co-dependent nature of the social determinants of health and illness. Research examining participation in population-based studies has not yet fully integrated this perspective into the analysis such that social heterogeneity remains largely hidden. The interdisciplinary research project AdvanceRecruitment focuses on participation in the German National Cohort (GNC) from an intersectional perspective to examine which individual and collective factors determine a decision for or against participation. Methods: A selective sampling strategy was employed to recruit interview participants (n = 73) according to age, participation, gender and geographical location from the overall GNC study sample. Individual GNC study centres were responsible for recruitment. Qualitative, semi-structured interviews with both participants (n = 61) and non-participants (n = 12) explored their motivations to participate, decision-making processes and experiences at the study centre. Interviews were recorded, transcribed verbatim and analysed through thematic and intersectional analyses. Results: Rationales for or against study participation do not primarily vary according to identity-based criteria such as gender or age, but are shaped by a complex assemblage of individual health action, personal biography, experiences of illness and vulnerability, possibilities for social inclusion, available resources and cultural capital. These factors can be better understood through their interrelation in an integrative analysis. Discussion: Intersectional approaches allow for a nuanced, complex understanding of study participation which should be considered when developing strategies for recruitment. Key messages: Intersectionality contributes to a more nuanced, complex understanding of study participation. Intersectional approaches can aid the development of strategies for recruitment.